2020
DOI: 10.1002/chem.202001578
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Stem Cell Potency of Nickel(II)‐Polypyridyl Complexes Containing Non‐steroidal Anti‐inflammatory Drugs

Abstract: We report the breastc ancer stem cell (CSC) potency of two nickel(II)-3,4,7,8-tetramethyl-1,10-phenanthroline complexes, 1 and 3,containingthe non-steroidalanti-inflammatoryd rugs (NSAIDs), naproxen and indomethacin, respectively.T he nickel(II) complexes, 1 and 3 kill breast CSCs and bulk breast cancer cells in the micromolar range. Notably, 1 and 3 display comparable or better potency towards breast CSCs than salinomycin,a ne stablished CSC-activea gent.T he complexes, 1 and 3 also display significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…This suggests a monodentate binding mode for the carboxylic acid moiety on flufenamic acid to the nickel(II) centre in 1 and a mixed monodentate-bidentate binding mode for 2 (as shown in Figure 1 ). The carboxylic acid group binding mode assignment for 1 and 2 is consistent with previous studies on structurally similar nickel(II)-polypyridyl complexes containing flufenamic acid and other NSAIDs [ 19 , 26 ]. The UV-vis spectra of 1 and 2 (50 µM) in PBS:DMSO (100:1) displayed intense signals between 277–288 nm associated to π–π* and metal-perturbed π–π* transitions originating from the flufenamic acid and 3,4,7,8-tetramethyl-1,10-phenanthroline or 4,7-diphenyl-1,10-phenanthroline units ( Figure S2 ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This suggests a monodentate binding mode for the carboxylic acid moiety on flufenamic acid to the nickel(II) centre in 1 and a mixed monodentate-bidentate binding mode for 2 (as shown in Figure 1 ). The carboxylic acid group binding mode assignment for 1 and 2 is consistent with previous studies on structurally similar nickel(II)-polypyridyl complexes containing flufenamic acid and other NSAIDs [ 19 , 26 ]. The UV-vis spectra of 1 and 2 (50 µM) in PBS:DMSO (100:1) displayed intense signals between 277–288 nm associated to π–π* and metal-perturbed π–π* transitions originating from the flufenamic acid and 3,4,7,8-tetramethyl-1,10-phenanthroline or 4,7-diphenyl-1,10-phenanthroline units ( Figure S2 ).…”
Section: Resultssupporting
confidence: 88%
“…The latter showed that [Ni( N , N -diethyldithiocarbamate) 2 (1,10-phenanthroline)] acted in a similar way to shikonin, a well-established necroptosis-inducer [ 17 ]. More recently we reported a series of nickel(II)-polypyridyl complexes bearing the non-steroidal anti-inflammatory drugs (NSAIDs) naproxen and indomethacin, with micromolar potency towards breast CSCs [ 19 ]. Mechanistic studies showed that the nickel(II) complexes triggered breast CSC death via a cyclooxygenase-2 (COX-2)-dependent pathway and in a manner that is blocked by necroptosis inhibitors [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there is a plethora of cobalt-NSAID complexes, such as those with tolfenamic acid [ 23 ], diflunisal, niflumic acid, flufenamic acid, mefenamic acid [ [26] , [27] , [28] ], diclofenac [ 15 , 16 , 29 ] and naproxen [ 30 ]. There is also a great number of transition metal complexes with indomethacin ligands [ 21 ], including manganese(II) [ 31 ], nickel(II) [ 32 , 33 ], copper(II) [ 34 , 35 ], tin(IV) [ 36 ] and zinc(II) complexes [ 37 ]. Another reason for the study of metals and their complexes is also their potential use in diagnostics which was also already used for detection of coronavirus MERS-CoV [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nickel complexes could be applied as valuable alternatives to anticancer platinum agents. Indeed, nickel-incorporated complexes have shown anticancer properties in prostate, breast, lung, and colon cancer cells [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%